(untitled) (Research, Society and Development, 2021)
The world dairy cattle industry has advanced, but in Brazil, the quality of milk is a barrier to the strengthening of the chain. Thus, the objective of this research was to institute an action plan in ten dairy farms in the southern region of Brazil, which produced low quality milk, and to monitor changes in quality and economic gain, during one year. Critical points were identified and an action plan based on good agricultural practices and mastitis control was instituted. Monitoring consisted of collecting and analyzing milk samples for levels of fat, protein, somatic cell count and standard plate count. After twelve months, there was an increase (p<0.05) in the levels of fat and protein and a reduction (p<0.05) in the somatic cell count and in the standard plaque count. The action plan improved the quality of milk and, therefore, reduced the disposal of milk in the environment, and increased the profitability of the properties studied.